2014
DOI: 10.5194/nhess-14-1125-2014
|View full text |Cite
|
Sign up to set email alerts
|

Non-stationarity in annual and seasonal series of peak flow and precipitation in the UK

Abstract: Abstract. When designing or maintaining an hydraulic structure, an estimate of the frequency and magnitude of extreme events is required. The most common methods to obtain such estimates rely on the assumption of stationarity, i.e. the assumption that the stochastic process under study is not changing. The public perception and worry of a changing climate have led to a wide debate on the validity of this assumption. In this work trends for annual and seasonal maxima in peak river flow and catchment-average dai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 38 publications
0
93
0
5
Order By: Relevance
“…For example, hydrometric monitoring networks were often installed in response to recent floods or recent droughts, which causes such extreme periods not appear in the observational data. This can be seen in the UK and Ireland, where the gauging network expanded from the 1970s onwards, a period with drought conditions and particularly few floods which is considered to influence the outcomes of trend analyses performed (Hannaford and Marsh, 2008;Murphy et al, 2013;Prosdocimi et al, 2014). Another factor resulting in similar biases are changing societal priorities and/or financial constraints, which sometimes cause gauges to be closed down (e.g.…”
Section: Observation Biases and Data Opportunitiesmentioning
confidence: 99%
“…For example, hydrometric monitoring networks were often installed in response to recent floods or recent droughts, which causes such extreme periods not appear in the observational data. This can be seen in the UK and Ireland, where the gauging network expanded from the 1970s onwards, a period with drought conditions and particularly few floods which is considered to influence the outcomes of trend analyses performed (Hannaford and Marsh, 2008;Murphy et al, 2013;Prosdocimi et al, 2014). Another factor resulting in similar biases are changing societal priorities and/or financial constraints, which sometimes cause gauges to be closed down (e.g.…”
Section: Observation Biases and Data Opportunitiesmentioning
confidence: 99%
“…To give a representation of the potential for high rainfall in each year and season the 99th percentile of the daily rainfall series for each year and season were used for each catchment. In a national scale study, Prosdocimi et al [2014] had found that the 99th percentile of the annual catchment averaged daily rainfall series was significantly correlated to block maxima values for most catchments in the UK.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…As discussed in Prosdocimi et al [2014] and later in this work, the record length available for annual maxima series (typically around 35 years in the UK) is not large enough to allow for an unequivocal detection and attribution of trends via statistical testing, and the analysis of such block maxima can be highly influenced by anomalies in the data series. Beside block maxima, peaks-over-the threshold series (POT), also known as a Partial Duration Series (PDS), are frequently used to assess the behavior of extreme events [see Madsen et al, 1997;Lang et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, comparing the annual with the seasonal distributions we encountered the problem of cross-over in the probability plot: the annual distribution must always lie on or above the highest seasonal distribution (Waylen, and Woo 1982, Durrans et al 2003, Baratti et al 2012, Prosdocimi et al 2014. For example, the probability of one peak value being exceeded in an entire year must be higher than the probability of the same value being exceeded in one season.…”
Section: Introductionmentioning
confidence: 99%